(untitled) (Baghdad Science Journal, 2024)
Nosocomial infection is acquired contamination of hospitals and health care units caused by multidrug resistant bacteria. Currently, bacterial resistance to antimicrobial medication represents a complicated public health problem. Recent studies on the antimicrobial activity of silver nanoparticles (AgNPs) attracted researchers worldwide to focus on the safe synthesis of AgNPs as antimicrobial agents against multidrug resistant bacteria. The antimicrobial efficacy of AgNPs on pathogenic bacteria isolated from clinical cases of acquired hospital infection was targeted in this project. Fifty specimens of stool were collected through private laboratories in Baghdad from patients who suffered diarrheal symptoms. Bacterial isolation, identification, and characterization via culturing on MacConkey agar, Salmonella shigella agar, and IMVic analysis were done besides, using polymerase chain reaction (PCR) through amplifying inf B gene for molecular characterization. The obtained isolates were tested for antimicrobial sensitivity via disk diffusion assay against; Gentamycin, Amoxicillin, Tetracycline, Ceftriaxone and a suspension of silver nanoparticles (1mM AgNo3 reduced by 1% tri-sodium citrate). Results of isolation and IMVic showed the obtained isolates were Klebsiella spp., Enterobacter spp., Citrobacter spp., and PCR assay confirmed their pathogenicity. Disc diffusion assay showed the sensitivity of the isolates (mm); Gentamycin (24.94 ± 0.1), Amoxicillin (2.11 ± 0.13), Tetracycline (12.15 ± 0.1), Ceftriaxone (12.35 ± 0.1). Whereas, all isolates are sensitive to AgNPs (24.12 ± 0.3). This result of the antimicrobial effect of AgNPs on nosocomial infection promises for developing AgNPs solution as a product used in the sterilization of furniture, floors and hospital water cycles